PENGARUH PROFITABILITAS, LEVERAGE, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP INCOME SMOOTHING: STUDI EMPIRIS PADA PERUSAHAAN PENERBANGAN TERBAIK ASIA - Purnomo, Nadia (Media Akuntansi dan Perpajakan Indonesia, 2020)
Airlines company particularly Asia’s airlines has dealing hard times especially when global crisis in 2008, that impacts towards aviation. Companies would do anything to maintain their existence. One of them is to perform income smoothing practices. An evidence found that one of the top airlines companies according to SKYTRAX has been performing income smoothing practices in the year of 2018, that was PT Garuda Indonesia. This indicating that others top airlines companies as well potentially performing income smoothing to maintain companies wholeness and even achieving to be top Asia’s airlines companies. This research aims to determine factors that influence the income smoothing practice in Asia’s top airlines companies. The variable used in this research are profitability, leverage, and institutional ownership. This research used quantitative approach with the use of multiple linear regression analysis technique. This research used 2008-2018 annual report period observed from eleven Asia’s airlines companies. The sampling method used in this research is purposive sampling with 121 data. The results show that profitability, leverage, and institutional ownership have a negative effect on income smoothing.